PERANCANGAN SISTEM GPS PEMANTAU KECEPATAN KENDARAAN UNTUK PENCEGAHAAN KECELAKAAN PADA SISWA SMK TRITECH INFORMATIKA MEDAN - Leman, Dedi; Nababan, Labuan (Jurnal Sistem Informasi Kaputama (JSIK), 2019)
In adolescence humans cannot be called adults but cannot be called children. Adolescence is the transition period of humans from children to adults. In this time, sometimes someone is looking for identity, a vehicle is a means of land transportation that is very useful in daily life, especially work that demands mobility. But the lack of a warning system and supervision of drivers often makes the vehicle a killing machine. To reduce the number of accidents due to motorists who like to exceed safe speed limits, it is necessary to monitor drivers to give a warning. With the existence of this system, it is expected that the related parties can find out the behavior of drivers and provide a warning if it is proven to often violate the safe speed limit set. The test results of SkyNav SKM53 GPS speed data give the smallest error value of 3.851 km / hr and the biggest error is 9.089 km / hr. This error can be corrected by multiplying the GPS speed data with a constant of 1.1457 which is a graphical gradient of the GPS speed ratio of the vehicle speed resulting in the smallest error of 1.467 km / h and the biggest error of 3.173 km / hr.